ASAL USUL BAHASA - Mega Arfriani Sihite; Putri Patricia Novelina Purba; Silvina Noviyanti (STKIP Subang, 2024)
The Origin of Language is one of the major questions in the study of linguistics, anthropology, and human evolution. Various theories have been proposed to explain how and when human language emerged. This article aims to thoroughly examine the main theories regarding the evolution of language, including monogenesis and polygenesis, as well as biological approaches that see brain development as key in the evolution of language ability. The study uses a qualitative method with literature analysis to identify and compare the views of various experts. The results indicate that while there is no absolute consensus on the origin of language, multidisciplinary perspectives offer a more comprehensive understanding. In conclusion, the evolution of language is a complex process involving biological, social, and cognitive factors.